Crime mapping through digital data analysis from intermediate repository by crowd sourcing - Aunamika, Sabiha Islam; TIthi, Samrin Sultana; Dev, Prema (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.